2019
DOI: 10.1080/02619768.2019.1566315
|View full text |Cite
|
Sign up to set email alerts
|

Is teacher attrition a poor estimate of the value of teacher education? A Swedish case

Abstract: Far from all who complete teacher education end up working as teachers throughout their entire career. At first sight the value of teacher education, in terms of efficiency, seems to be a failure. In the present article we argue that teacher attrition, when defined as whether one is working as teacher or not, is a too blunt measure to gauge whether teacher education has been valuable. With a unique dataset, where we have detailed information on 87 Swedish teacher graduates' working life across 23 years, we can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Coherently with our hypothesis, in the current sample of Italian teachers, work engagement was negatively associated with burnout. It is an expected result in line with abundant international findings that have shown that the more workers are engaged, the less burnout symptoms they experience during their career (e.g., [26][27][28][43][44][45][46][47]). Furthermore, our findings have shown that engaged teachers express high confidence towards professional training.…”
Section: Between Teachers' Engagement and Confidence In Training: The...supporting
confidence: 69%
See 1 more Smart Citation
“…Coherently with our hypothesis, in the current sample of Italian teachers, work engagement was negatively associated with burnout. It is an expected result in line with abundant international findings that have shown that the more workers are engaged, the less burnout symptoms they experience during their career (e.g., [26][27][28][43][44][45][46][47]). Furthermore, our findings have shown that engaged teachers express high confidence towards professional training.…”
Section: Between Teachers' Engagement and Confidence In Training: The...supporting
confidence: 69%
“…Both work engagement and burnout have an impact on teachers' attitudes towards their job: while engaged teachers are motivated to improve their professional competence, burned-out teachers are more likely to reject professional learning opportunities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, during the adjustment period of new teaching staff, it is likely that this might fuel certain problems in the school units' climate (Saiti and Saitis, 2012). As regards attracting teachers, relevant research has proven that, despite the requirement for recruiting a sizeable number of new teachers in the years to come, it is expected to be a hard and demanding issue (Luekens in: Robertson and Smith, 2001;Carless, 2007;Aragon, 2016;UNESCO Institute of Statistics, 2016;Carlsson et al, 2019). This is due to the fact that in countries where young people have the opportunity to choose among a plethora of various job positions, they are reluctant to work in schools, opting for other more attractive occupations (in terms of wages, benefits, working conditions, social recognition, and personal satisfaction).…”
Section: Staffingmentioning
confidence: 99%
“…This is mostly due to schools' needs (Arviv Elyashiv et al, 2019). Thus, while it has been documented that many teachers are drawn to the teaching profession due to intrinsic motivations (Arviv Elyashiv & Gal, 2017;Carlsson et al, 2019;Watt, & Richardson, 2008), external rewards seem to matter too in decision making; the absence of appropriate rewards may lead to dissatisfaction and eventually to attrition (e.g. Borman & Dowling, 2008;Dupriez et al, 2016;Johnson & Kardos, 2008;Newberry & Allsop, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These studies mention various features of teachers' work environment that increase the likelihood of leaving teaching, such as: heavy workload; lack of autonomy; lack of opportunities to participate in decision making; difficulties in managing relationships with colleagues, students, and their parents; lack of collegial or principal support; and, lack of opportunities for professional development (e.g. : Borman & Dawling, 2008;Boyd et al, 2011;Carlsson et al, 2019;Geiger & Pivovarova, 2018;Newberry & Allsop 2017).…”
Section: Deserción De Docentes: Capital Humano Y Condiciones De Empleo -¿Son Importantes?mentioning
confidence: 99%